The Prognostic Model and Drug Sensitivity of LKB1-Mutant Lung Adenocarcinoma Based on Immune Landscape - Wang, Guanghui; Zheng, Haotian; Zhao, Xiaogang; Wang, Yadong; Zeng, Yukai; Du, Jiajun (Frontiers in Molecular Biosciences, 2022)
Background: Lung cancer is the most common cause of cancer-related deaths worldwide, LKB1 mutant lung adenocarcinoma (LUAD) is a unique subtype. LKB1 mutations cause functional changes in a variety of cell processes including immunity that significantly affect prognosis. But to date, the potential role of immunity in LKB1 mutant LUAD prognosis is not well understood. Methods: In this study, we systematically analyzed immune-related genes in LUAD samples from The Cancer Genome Atlas (TCGA) database. ESTIMATE and CIBERSORT algorithms were used to explore immune microenvironment. A prognostic risk model was constructed, prognostic, immune function, drug sensitivity and model specificity analyses were performed to identified the effectiveness of the model. Results: Our results showed that LKB1 mutant suppressed the immune function in LUAD. A 3-gene signature was constructed to stratify patients into two risk groups. The risk score was an independent predictor for overall survival (OS) in multivariate Cox regression analyses (Hazard ratio (HR) > 1, P = 0.002). Receiver operating characteristic (ROC) curve analysis confirmed the risk score has better capacity than clinicopathological characteristics. Functional analysis revealed that immune status was different between two risk groups. ZM.447439 was an appropriate treatment for the high-risk group patients. Moreover, this risk model was only suitable for LKB1 mutant lung adenocarcinoma, and it performed very poorly in patients with LKB1 wild lung adenocarcinoma. Conclusions: In conclusion, our findings indicate the potential role of immunity in LKB1 mutant LUAD, providing novel insights into prognosis and guiding effective immunotherapy.